Kombinasi Metode Entropy dan Simple Additive Weighting (SAW) dalam Pemilihan Dosen Pembimbing Skripsi - Nisa, Halimatun; Aulia, Fitrahuda; Rayhan, Annisa (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2022)
In the preparation of the thesis, students need a supervisor as a place of consultation in completing the thesis. The supervisor should be a person who mastered the field in accordance with the topic of student thesis, so that the guidance process can run optimally. Thesis is one of the graduation requirements to obtain a bachelor's degree. Generally, the selection of thesis supervisors is decided by the study program through a meeting of lecturers to determine which lecturers are in accordance with the title and description of the students who took the thesis course. To solve this problem, a solution is needed that can take into account the specifications of lecturer expertise that suits the needs of students. The Entropy method is an alternative to solve this problem. This method was chosen because it is able to select the best alternatives from a number of alternatives, in this case the intended alternative is to be a supervisor and examiner based on the specified criteria. Research is carried out by looking for the weight value for each attribute, then a casting process is carried out that will determine the optimal alternative, namely the four lecturers whose specification values are highest.Keyword: Decision Support System, Entropy, Thesis